Reasonable Education in the Book of Tarbiyatul Aulad by Abdullah Nashih Ulwan and Its Implications in Modern Education - Tri Yugo (Penerbit Hellow Pustaka, 2024)
This research aims to explore the concept of intellectual education in the book